Untangling areas of improvement in secondary prevention of ischemic stroke in patients with atrial fibrillation - F Sánchez-Sáez; CL Rodríguez-Bernal; I Hurtado; J Riera-Arnau; A Garcia-Sempere; Salvador Peiró; G Sanfélix-Gimeno (Scientific Reports)
Abstract Improvement of post-stroke outcomes relies on patient adherence and appropriate therapy maintenance by physicians. However, comprehensive evaluation of these factors is often overlooked. This study assesses secondary stroke prevention by differentiating patient adherence to antithrombotic treatments (ATT) from physician-initiated interruptions or switches. We analyzed a population-based retrospective cohort (n = 10,343) of post-stroke patients with atrial fibrillation using the VID database (2010–2017). Secondary prevention was evaluated based on patients’ primary and secondary adherence to ATT at two years (percentage of days covered—PDC—and persistence/discontinuation) and physician prescription patterns (initiation, interruption, switching, restart). E-prescription and dispensing data were linked. Three ATT strategies were identified: oral anticoagulants (OAC), antiplatelets (APT), or combination therapy (OAC + APT), prescribed to 54%, 23%, and 17% of patients, respectively. Primary adherence was high for all ATTs (≈90%). OAC discontinuation was highest (16%), but frequently restarted (73.4%). APT treatment was interrupted the most (14%) and restarted the least (38.5%) by physicians, followed by OAC (interrupted in 11%, restarted in 65%). Overall, 17% of patients switched treatments, with OAC + APT being switched the most (76%), mainly to OAC (53.8%). Identifying areas for improvement in secondary stroke prevention requires considering both patient adherence and physician prescription patterns (initiation, interruptions, and restarts).